Capacity Building Model Strategy for Developing Lecturer Integrity and Competency in Efforts to Fulfill International Standards - Hikmat Zakky Almubaroq; Agus Sudarya; Lutfi Adin Affandi (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research aims to obtain a lecturer development model to increase the global competitiveness of higher education in the aspects of integrity and competency based on international (global) standards. World Class University (WCU) as a reference for ranking, recognition and assessment of universities on a world scale. In other words, universities are ranked by institutions that have an international reputation. This mixed method research with two quantitative and qualitative stages targeted 650 UPI lecturers who had doctoral qualifications. Next, a sample of 10% or 65 people from the population was taken. This research uses mixed methods with two quantitative and qualitative stages. The data collection stages were carried out first, Preparation for field studies, Focus Group Discussion (FGD) was carried out to analyze policy issues for developing the integrity and competence of international standard lecturers, Surveys, interviews and filling out questionnaires, documentation studies within the scope of the Indonesian University of Education (UPI) and finally carried out Analysis of Survey Results Data using descriptive statistical techniques and qualitative data classification techniques. The research results show that integrity, competence and performance are very important components and variables in developing human resources for UPI lecturers to achieve World Class Universities (WCU). The influence between variables according to SEM shows that the direct variable integrity on competence is only 0.458, the influence of integrity on performance is 0.446 and the influence of competence on performance is 0.460. or it can be concluded that everything is in a moderate position.